Prevalence and Predictors of Multimorbidity Among Older Adults Attending the General Outpatient Clinic of Federal Teaching Hospital Birnin-Kebbi - Hope Abitare (Journal of Family Medicine and Health Care, 2026)
Multimorbidity is an emerging public health challenge associated with poor health outcomes, increased healthcare utilization, and rising healthcare costs, particularly among older adults. Despite its growing burden, evidence on multimorbidity among older adults in Northwestern Nigeria remains limited. This study determined the prevalence and predictors of multimorbidity among older adults attending the General Outpatient Clinic of the Federal Teaching Hospital, Birnin-Kebbi, Nigeria. A hospital-based cross-sectional study was conducted among 327 adults aged 60 years and above selected using systematic random sampling. Data were collected using a structured interviewer-administered questionnaire, while selected clinical information was verified from participants' medical records where applicable. Descriptive statistics were used to summarize participants' characteristics and estimate the prevalence of multimorbidity. Associations between independent variables and multimorbidity were assessed using the Chi-square test, while multivariable binary logistic regression analysis identified independent predictors. Statistical significance was set at p < 0.05. The prevalence of multimorbidity was 55.7%. Hypertension, diabetes mellitus, and arthritis were the most frequently reported chronic conditions. At the bivariate level, age, sex, marital status, educational attainment, health insurance status, physical activity, body mass index, polypharmacy, recent hospital admission, frequency of clinic attendance, and difficulty obtaining prescribed medications were significantly associated with multimorbidity ( p < 0.05). After adjustment for potential confounders, advanced age (≥70 years), female sex, insufficient physical activity, polypharmacy, and recent hospital admission remained significant independent predictors of multimorbidity. Multimorbidity was found to be highly prevalent among older adults attending the General Outpatient Clinic of the Federal Teaching Hospital, Birnin-Kebbi and is influenced by both modifiable and non-modifiable factors. Routine screening for multimorbidity, promotion of healthy lifestyle behaviours, regular medication review, and implementation of integrated, person-centred chronic disease management strategies are recommended to improve health outcomes among older adults.